AIDA (Attention, Interest, Desire, Action) as a Social Media Marketing Strategy towards Customer Loyalty of Pelakor Laundry Business. - Muhammad Izzatul Haq; Mohammad Adrian; Katty Cintiasari; Fernando Hosse Fahrezi; Mahrinasari MS (MINOVa Ditria Jaya, 2025)
This study aims to explore the application of the AIDA model (Attention, Interest, Desire, Action) as a social media marketing strategy in enhancing customer loyalty at the